2014
DOI: 10.1101/cshperspect.a015990
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic Origins: How and When Was the Mitochondrion Acquired?

Abstract: Comparative genomics has revealed that the last eukaryotic common ancestor possessed the hallmark cellular architecture of modern eukaryotes. However, the remarkable success of such analyses has created a dilemma. If key eukaryotic features are ancestral to this group, then establishing the relative timing of their origins becomes difficult. In discussions of eukaryote origins, special significance has been placed on the timing of mitochondrial acquisition. In one view, mitochondrial acquisition was the trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 87 publications
(110 reference statements)
2
87
0
Order By: Relevance
“…Previously, the best that could be achieved was to generate elegant, but ultimately highly speculative, models of eukaryogenesis. Resolving the order of transitions is challenging but remains one of the crucial questions concerning the steps of eukaryogenesis (Poole and Gribaldo, 2014). With the recent improvements in analysis of genomic data as well as the identification of novel microbial lineages, a more robust evidence-based scientific path can be forged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the best that could be achieved was to generate elegant, but ultimately highly speculative, models of eukaryogenesis. Resolving the order of transitions is challenging but remains one of the crucial questions concerning the steps of eukaryogenesis (Poole and Gribaldo, 2014). With the recent improvements in analysis of genomic data as well as the identification of novel microbial lineages, a more robust evidence-based scientific path can be forged.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most exciting implication for the presence of orthologues for both membrane-trafficking machinery and cytoskeleton proteins in these archaeal lineages is that FECA might have already possessed the genetic potential to develop phagocytosis. The origin of this trait was a key step in eukaryogenesis (Koonin, 2015;Poole and Gribaldo, 2014).…”
Section: Towards Revealing the Prokaryotic Origins Of Eukaryotic Cellmentioning
confidence: 99%
“…The last half-century of cellular and molecular evolutionary research has conclusively shown that mitochondria are descended from an a-proteobacterial endosymbiont that took up residence within a host cell prior to the last eukaryotic common ancestor (LECA) [1]. However, the precise phylogenetic position of the mitochondrial lineage among a-proteobacteria [2,3], as well as the nature of the host lineage that engulfed it [4], remain active areas of debate and investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Because this process occurred in the eukaryotic stem group (for which all representatives are extinct), examining modern taxa remains uninformative in this context (figure 1). Several outstanding questions thus remain [6]; in particular, how and when were mitochondria acquired relative to the defining features of eukaryotes? To the extent that eukaryotic features can be considered sequelae to endosymbiosis, progress can be made in answering these questions.…”
Section: Introductionmentioning
confidence: 99%